2020
DOI: 10.1371/journal.pone.0233066
|View full text |Cite
|
Sign up to set email alerts
|

High polymerase ε expression associated with increased CD8+T cells improves survival in patients with non-small cell lung cancer

Abstract: DNA replicase polymerase ε (POLE) is critical in proofreading and correcting errors of DNA replication. Low POLE expression plays a pivotal role in accumulation of mutations and onset of cancer, contributing to development and growth of tumor cells. The aim of this study is to reveal the survival, alternative genes and antitumoral immune activities in nonsmall cell lung cancer (NSCLC) patients with low POLE expression and provide treatment strategies that can increase their survival rates. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Ultraviolet-related characteristics are almost only found in the squamous cell carcinoma subtype [ 20 ]. Min et al reported that the V1446fs frameshift mutation of POLE was the site associated with the highest incidence of NSCLC (56.8%) [ 53 ]. In a study of the Chinese population, P286R and F699Vfs*11 were identified as the hotspot mutations of POLE in lung cancer, whereas the hotspot mutations recorded in the COSMIC database are P286R and V411L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet-related characteristics are almost only found in the squamous cell carcinoma subtype [ 20 ]. Min et al reported that the V1446fs frameshift mutation of POLE was the site associated with the highest incidence of NSCLC (56.8%) [ 53 ]. In a study of the Chinese population, P286R and F699Vfs*11 were identified as the hotspot mutations of POLE in lung cancer, whereas the hotspot mutations recorded in the COSMIC database are P286R and V411L.…”
Section: Introductionmentioning
confidence: 99%
“…Rizvi et al reported that four NSCLC patients with POLE mutation achieved a progression free survival of 8–14 months after treatment with pembrolizumab, suggesting that the efficacy of anti-PD-1 therapy is higher in NSCLC with POLE mutation [ 69 ]. Min et al also showed that the level of infiltrating T cells in POLE -mutated NSCLC is increased, resulting in a favorable prognosis [ 53 ]. The KEYNOTE-028 study reported that a POLE -mutated patient with advanced EC achieved partial remission after 8 weeks of treatment with pembrolizumab and achieved continuous remission for more than 14 months [ 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, SLC2A1 was significantly postively correlated with Th2 CD4 + T cells and significantly negtively correlated with CD 8 + T cell, M2 macrophages and B cell in a variety of cancers. High expression of SLC2A1 can affect the prognosis of gastric cancer by suppressing CD8 + T cells and B cells ( Min et al, 2021 ). Additionally, we found that SLC2A1 was significantly associated with MDSC infiltration in ACC, LUAD, TGCT, and PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that SLC2A1 inhibition blocks the growth of RB1-positive triple-negative breast cancer ( Wu et al, 2020 ). Min et al found that SLC2A1 improved the survival of gastric cancer patients by suppressing CD8 + T cells and B cells ( Min et al, 2021 ). However, research on SLC2A1 is still confined to a few cancer species.…”
Section: Introductionmentioning
confidence: 99%
“…PolE mutations are most frequently found in colorectal cancer (1-3%) and endometrial cancer (6-12%), and rarely found in lung, breast, brain, prostate, kidney, ovarian, bone, and gastric cancers [3]. In addition, other somatic point mutations in the polymerase domain of PolE (R567C, K593C, S595P, E611K, and L621F) and a deletion frameshift in the middle region of the PolE gene (V1446fs *3) are possible pathogenic factors in cancer [20,21]. Mutations in non-catalytic subunits of Polε, PolE2, PolE3 and PolE4, are rare in cancer and their involvement in ultramutagenesis is not clear.…”
Section: Pole Mutations Generate Ultramutation Genotype In Cancermentioning
confidence: 99%